2007
DOI: 10.1063/1.2790380
|View full text |Cite
|
Sign up to set email alerts
|

Two-glassy-phase bulk metallic glass with remarkable plasticity

Abstract: Using the computational-thermodynamic approach, the potential compositions of Zr-Cu-Ni-Al alloy system exhibiting the two-liquid miscibility phase equilibrium in the liquid temperature region have been identified. The resulting Zr base bulk metallic glasses show a microstructure of two microscaled glassy phases. The glass possesses a remarkable macroscopic plastic strain of 30% at room temperature. The gain of mechanical properties is attributed to the unique glassy structure correlated with the chemical inhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 21 publications
3
62
0
Order By: Relevance
“…Similar results were also found in the ZrCu NiAl 10) and TiZrCuNiSn 11) alloy systems. However, in a recent work, Park et al 12) reported a nanoscale phase separation when adding above 15 at% Y to the CuZrAl based alloy, forming a composite of Cu-rich and Y-rich glassy phases, which does not exhibit any plastic strain upon deformation.…”
Section: Introductionsupporting
confidence: 76%
“…Similar results were also found in the ZrCu NiAl 10) and TiZrCuNiSn 11) alloy systems. However, in a recent work, Park et al 12) reported a nanoscale phase separation when adding above 15 at% Y to the CuZrAl based alloy, forming a composite of Cu-rich and Y-rich glassy phases, which does not exhibit any plastic strain upon deformation.…”
Section: Introductionsupporting
confidence: 76%
“…(iv) Microalloying to produce the amorphous phase separation 19 . This was achieved in some BMGs by adding elements with a large difference in its mixing enthalpy when binding with the main elements of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Due to similarity of the current composition with that of the Inoue's alloy, [19] the Poisson's ratio should not be greatly different. Thus, these three possibilities should be excluded.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] Further, based on the thermodynamic calculation, microscale phase separated Zr-based BMGs (Zr 63.8 Ni 16.2 Cu 15 Al 5 and Zr 65.8 Ni 15.8 Cu 8.4 Al 10 ) with a marked plasticity have been successfully developed by the authors. [15,16] And a unique mechanism operative in the phase-separated BMG, i.e, the effective hindering of the hard glassy phase on the propagating of shear bands, has been suggested. This indicates that by designing the compositions based on the thermodynamic calculation, some monolithic BMGs can deform plastically through the formation of phase-separated microstructures.…”
mentioning
confidence: 99%